La personalidad, ¿paradigma o sistema? - Prieto Zamora, José María (1980)
This paper is concerned with a comprehensive and enlarged personality concept in ordain to emphasize its usefulness in theoretical and applied multivariate psychology. Approaching it as a paradigm (accepted model for prediction and assessment of behaviours and dispositions) eight axioms are stated that become the backbone for any research followed up through multifactorial procedures. Likewise, the disciplinary matrix is pointed out, making sense of those shared elements and experimental attainment which connect Multidimensional Personality Theory and General Psychology. Finally, several viewpoints are looked over since traits (into the General Systems Theorys context) are reviewed as sub-systems which transduce, transform and integrate behavioural information. So personality is figured out as a dynamic, complex and multi-leveled supra-system. Traits become not mere hypothetical constructs but modulating focuses of influence and determination